Do Hemogram Parameters Correlate With The Level and Location of The Obstruction in Acute Mesenteric Ischemia Patients? - (:unkn) unknown (My University, 2019)
Background and Objectives: Acute mesenteric ischemia (AMI) is a disease with high mortality that needs early diagnosisand management. There has been a recent trend in the search for a fast prognostic tool for AMI. Hemogram parametersare widely used tools in emergency departments since they are inexpensive and fast.In this study our primary objective was to evaluate the significance of hemogram parameters in predicting the level ofobstruction in superior mesenteric artery (SMA) and truncus coeliacus (TC). Our secondary objective was to evaluate thesignificance of hemogram parameters in predicting the location of obstruction in AMI patients.Methods: In this retrospective study, we reviewed medical records of 214 AMI patients including; hemoglobin,hematocrit, platelet, mean platelet volume, red blood cell distribution width counts and computed tomography scanresults. Patients with missing data were excluded and 208 patients were enrolled.Results: Among 208 AMI patients, 123 (59.1%) were male. The median age was 68 (IQR: 59, 77). There were no significantdifferences between the obstruction level groups for the hemogram parameters neither in SMA nor in TC. The differencebetween obstruction location groups for hemogram parameters were clinically insignificant.Conclusion: We found that hemogram parameters do not correlate with the level and location of the obstruction in AMIpatients. Other pathophysiological processes seem to be more important for the survival of those patients.

Amaç: Akut mesenterik iskemi (AMİ), erken teşhis ve tedaviye ihtiyaç duyan yüksek mortaliteye sahip bir hastalıktır. AMİ için hızlı bir prognostik araç araştırılmaktadır. Hemogram parametreleri ise; ucuz ve hızlı olduklarından, acil servislerde yaygın olarak kullanılan tanısal araçlardır. Bu çalışmadaki birincil amacımız, superior mezenterik arter (SMA) ve trunkus çöliyakustaki (TÇ) obstrüksiyon düzeylerinin öngörülmesinde, hemogram parametrelerinin öneminin değerlendirilmesidir. İkincil amacımız ise AMİ hastalarında obstrüksiyonun yerinin belirlenmesinde hemogram parametrelerinin öneminin değerlendirilmesidir. Yöntemler: Bu retrospektif çalışmada, 214 AMİ hastasının tıbbi kayıtları incelenerek; hemoglobin, hematokrit, trombosit, MPV, RDW değerleri ve bilgisayarlı tomografi sonuçları kaydedilmiştir. Kayıtlarında eksikleri olan hastalar dışlanmıştır ve 208 hasta çalışmaya dahil edilmiştir. Bulgular: 208 AMİ hastasının 123’ü (% 59.1) erkekti. Medyan yaş 68 idi (IQR: 59, 77). SMA’da ve TÇ’da obstrüksiyon düzeyi grupları arasında, hemogram parametreleri açısından anlamlı bir farklılık saptanmadı. Obstrüksiyon lokasyon grupları arasındaki fark da hemogram parametreleri açısından klinik olarak anlamlı değildi. Sonuç: AMİ hastalarında, hemogram parametrelerinin, obstrüksiyonun düzeyi ve lokasyonu ile ilişkili olmadığını tespit ettik. Diğer patofizyolojik süreçler, bu hastaların hayatta kalması için daha önemli gibi görünmektedir.
Akut Mezenter İskemi Hastalarında Hemogram Parametreleri Tıkanıklığın Düzeyi ve Yeri İle İlişkili midir ?
Keywords: Genel ve Dahili Tıp